Resistance and learning: the spiritualities that animate them - Méndez Méndez, José Mario (2022)
Resistances, educations and spiritualities are intertwined and mutually reinforced in the experience of social movements in Central America. This work gathers the les- sons learned from conversations carried out during the year 2022 with 12 resistance groups in different regions of Costa Rica. It is an initiative that is part of the project Educations, spiritualities and resistances: liberating pedagogical and socio-religious experiences for children and adolescents, attached to the Escuela Ecuménicade Ciencias de la Religión (National University, Costa Rica). The main objective is to identify the spiritualities that nurture resistances and educational practices.